Pattern Analyses on Women Entrepreneurship in Performance’s Services Industries: Malaysian and Australian Perspectives - Loo, Fung Ying; Wong, Edward Sek Khin (American-Eurasian Network for Scientific Information, Jordan, 2010)
The main aim of this paper is to examine why performance services industry is far being gender neutral. It discusses the feminist debate through the authors’ self-reflective accounts, which rely upon the application of certain concepts of justice, equality, and humanity. With the rise of feminist and then gender studies through the last quarter of the twentieth century, scholars began to indentify the male centrism in the discourse on performance services industry. As they have in many fields (music, literature, and anthropology, among others), strategies to remove or balance the male bias in the study of entrepreneur potency and power in performance services industries have generally fallen into three categories; scholars try to demonstrate that contemporary women have their own equally important entrepreneur power structures that are parallel or tangential to male structures; scholars try to insert women into male power structures; or scholars try to reinsert women and female power into the discourse on performance services industry. This being so, a central question for this paper is “Why is the performance services industry far from being gender neutral?” The authors argue that such issues need to be highlighted, as they perceives that society as it stands is still unfair to women, and that this unfairness should be addressed. The paper also identifies that there are still, unanswered questions as to whether discrimination against suitably qualified women for such positions are defensible according to the current principles of social justice.